Notch Signaling Pathway Is Activated in Motoneurons of Spinal Muscular Atrophy - Caraballo-Miralles, Víctor (Molecular Diversity Preservation International (MDPI), 2013)
Spinal muscular atrophy (SMA) is a neurodegenerative disease produced by low levels of Survival Motor Neuron (SMN) protein that affects alpha motoneurons in the spinal cord. Notch signaling is a cell-cell communication system well known as a master regulator of neural development, but also with important roles in the adult central nervous system. Aberrant Notch function is associated with several developmental neurological disorders; however, the potential implication of the Notch pathway in SMA pathogenesis has not been studied yet. We report here that SMN deficiency, induced in the astroglioma cell line U87MG after lentiviral transduction with a shSMN construct, was associated with an increase in the expression of the main components of Notch signaling pathway, namely its ligands, Jagged1 and Delta1, the Notch receptor and its active intracellular form (NICD). In the SMNΔ7 mouse model of SMA we also found increased astrocyte processes positive for Jagged1 and Delta1 in intimate contact with lumbar spinal cord motoneurons. In these motoneurons an increased Notch signaling was found, as denoted by increased NICD levels and reduced expression of the proneural gene neurogenin 3, whose transcription is negatively regulated by Notch. Together, these findings may be relevant to understand some pathologic attributes of SMA motoneurons.